Evaluation by thermogravimetry of the interaction of the poly(ethylene terephthalate) with oil-based paint - Dos Santos Dias, Diógenes [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clóvis Augusto [UNESP]; Kobelnikb, Marcelo (My University, 2015)
The recycling of post-consumer soft-drink bottles poly (ethylene terephthalate) (PET) has been used as an additive in paint containing alkyd resin. Samples of paint containing PET (PPET) were applied in a film form on slides, and its thermal properties were evaluated for thermogravimetry (TG). The thermal behavior of PPET, it was possible to identify that the maximum of PET added to the paint without a change in the film properties was 1%. The kinetic parameters such as activation energy (Ea) and pre-exponential factor (A) were calculated using the isoconversional Flynn - Wall - Ozawa method for samples containing 0.5 to 1.0% of PET. The kinetic analysis indicates that there was a variation in Ea values. The kinetic compensation effect (KCE), represented by the equation ln A = 0.105E - 0.21 for the first stage of thermal decomposition.
Keywords: Non-Isothermal Kinetic; Paint and PET; Paint oil-based; PET